ANALISIS SIKAP ILMIAH DALAM BUKU CONFIDENCE IN SCIENCE: KAPAN BULAN BERUBAH BENTUK? - desty putri (Fakultas Agama Islam Universitas Billfath, 2024)
The purpose of this study is to examine the integration of scientific concepts with the development of scientific attitudes and moral internalization through a narrative approach in the Confidence in Science reference book, entitled